A Christmas story 2 - Mauldin, Nat; Goldfine, Phillip B.; Levant, Brian; Stern, Daniel 1957-; Lemasters, Braeden 1996-; Travis, Stacey; Warner Premiere (Firm); Hollywood Media Bridge (Firm); Telvan Productions (Firm); Warner Home Video (Firm) (Burbank, CA : Distributed by Warner Home Video, 2012)
The original, traditional, one-hundred-percent, red-blooded, two-fisted, all-American Christmas continues five years later with Ralphie, Randy, Mom, and the old man. This time, Ralphie has his eyes fixed on a car. But trouble is sure to follow.
Title from container.
Videodisc release of the 2012 television production.
Sequel to: The Christmas story.
Release date: Oct. 30, 2012.
Special features: Catching up with Ralphie and his family; The house then and now; A Christmas story we all know and love; gag reel.
Director of photography, Jan Kiesser ; editor, Roger Bondelli ; music, David Newman.
Keywords: Families -- Drama; Gifts -- Drama; Automobiles -- Drama; Video recordings for the hearing impaired; Feature films; Comedy films; Christmas films; Video recordings with Spanish language options; Drama